Analysis of changes in the association of income and the utilization of curative health services in Mexico between 2000 and 2006 - Valencia-Mendoza Atanacio; Sosa-Rubí Sandra G; Danese-dlSantos Laura G (BMC Public Health, 2011)
Abstract Background A common characteristic of health systems in most developing countries is unequal access to health services. As a result, members of the poorest population groups often do not receive formal attention for health services, because they cannot afford it. In 2001 in Mexico, to address income-related differences in the use of health services, the government launched a major healthcare reform, which includes a health insurance program called Seguro Popular, aimed at improving healthcare access among poor, uninsured residents. This paper analyzes the before and after changes in the demand for curative ambulatory health services focusing on the association of income-related characteristics and the utilization of formal healthcare providers vs. no healthcare service utilization. Methods By using two nationally representative health surveys (ENSA-2000 and ENSANUT-2006), we modeled an individual's decision when experiencing an illness to use services provided by the (1) Ministry of Health (MoH), (2) social security, (3) private entities, or (4) to not use formal services (no healthcare service utilization). Results Poorer individuals were more likely in 2006 than in 2000 to respond to an illness by using formal healthcare providers. Trends in provider selection differed, however. The probability of using public services from the MoH increased among the poorest population, while the findings indicated an increase in utilization of private health services among members of low- and middle-income groups. No significant change was seen among formal workers -covered by social security services-, regardless of socioeconomic status. Conclusions Overall, for 2006 the Mexican population appears less differentiated in using healthcare across economic groups than in 2000. This may be related, in part, to the implementation of Seguro Popular, which seems to be stimulating healthcare demand among the poorest and previously uninsured segment of the population. Still, public health authorities need to address the remaining income-related healthcare utilization differences, the differences in quality between public and private health services, and the general perception that MoH facilities offer inferior services.